Revenge Tourism: Strategy To Increase The Number Of Tourist To Mount Bromo After The Fire - Uhai, Sabalius; Indriani, Novita; Darmiati, Made; Diwyarthi, Santi; Putri, Nia Rifanda (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to determine (1) the decline in tourist visits and government losses after the Bromo fire; and (2) revenge tourism as a strategy to increase the number of tourists to Mount Bromo after the fire. This research is qualitative-descriptive research. This research uses SWOT analysis. The results of this research show that (1) the level of tourist arrivals in the Mount Bromo area after the fire was around 40-60 percent of the total quota prepared, plus state losses due to the fire reached 89.7 billion which was calculated based on the number of visits, ticket prices, fees and length of closing time; and (2) the idea of a revenge tourism strategy can be a reference for returning enthusiasm for tourism to Mount Bromo after the fire. The strategy to increase tourists used includes the SO strategy through publication planning to convince tourists that the Mount Bromo area is safe and ready to visit, the WO strategy by displaying the image of 'safe travel' for visiting tourists, the ST strategy through government collaboration with the private sector to support sustainable Bromo tourism, and the WT strategy by providing education to tourism managers.